2022
DOI: 10.1094/pdis-02-21-0372-re
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Prochloraz Resistance in Fusarium fujikuroi from Heilongjiang Province in China

Abstract: Prochloraz is widely used to control the rice bakanae disease caused by Fusarium fujikuroi. The current study was aimed at monitoring the development of F. fujikuroi resistance to prochloraz in the Heilongjiang province, and at analyzing the fitness of F. fujikuroi strains with different resistance levels. The results indicated that the majority of the 89 F. fujikuroi strains collected from the Heilongjiang province were resistant to prochloraz, with resistance frequency reaching 92.1%. To assess the field res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…fragariae isolate to tebuconazole recorded 34.22 folds after 36 times selection in comparison to the sensitive isolate, according to (GU et al, 2010). Only seven F. fujikuroi strains were found to be prochloraz susceptible, while 82 strains were resistant, according to the findings of the study (Peng et al, 2022). The present investigation conducted to detect the resistance frequencies to DMI fungicides difenoconazole, tebuconazole and prochloraz among Fusarium oxysporum populations collected, to determine the half-maximal effective concentration (EC50) values for the resistant and sensitive isolates, respectively, and in the end to find out the effectiveness of certain fungicide mixtures to management DMI resistant populations.…”
Section: Introductionsupporting
confidence: 50%
“…fragariae isolate to tebuconazole recorded 34.22 folds after 36 times selection in comparison to the sensitive isolate, according to (GU et al, 2010). Only seven F. fujikuroi strains were found to be prochloraz susceptible, while 82 strains were resistant, according to the findings of the study (Peng et al, 2022). The present investigation conducted to detect the resistance frequencies to DMI fungicides difenoconazole, tebuconazole and prochloraz among Fusarium oxysporum populations collected, to determine the half-maximal effective concentration (EC50) values for the resistant and sensitive isolates, respectively, and in the end to find out the effectiveness of certain fungicide mixtures to management DMI resistant populations.…”
Section: Introductionsupporting
confidence: 50%
“…Because of the high selection pressure of these fungicides, however, resistance has been reported in a variety of pathogenic fungi 40‐43 . Several investigations found that the target gene Cyp51 was upregulated after treatment with triazole fungicides, and overexpression of Cyp51 gene causing triazole fungicide resistance has been reported in a series of plant pathogenic fungi, such as in B. cinerea , Colletotrichum gloeosporioides , and Fusarium fujikuroi 44‐46 . Our investigation found that natamycin significantly decreased the expression of Cyp51 , whereas the expression of Cyp51 was enhanced after flusilazole treatment.…”
Section: Discussionmentioning
confidence: 45%
“…[40][41][42][43] Several investigations found that the target gene Cyp51 was upregulated after treatment with triazole fungicides, and overexpression of Cyp51 gene causing triazole fungicide resistance has been reported in a series of plant pathogenic fungi, such as in B. cinerea, Colletotrichum gloeosporioides, and Fusarium fujikuroi. [44][45][46] Our investigation found that natamycin significantly decreased the expression of Cyp51, whereas the expression of Cyp51 was enhanced after flusilazole treatment. In addition, a previous study showed that flusilazole decreased the permeability of the cell membrane in S. sclerotiorum, 47 which was contrary to our result showing that natamycin enhanced the permeability of the cell membrane.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, the CYP51A paralogue is commonly altered or overexpressed in most phytopathogenic fungi with the resistance to DMIs, including A. fumigatus, 29,38 C. acutatum, 17 Venturia inaequalis, 39 Penicillium digitatum, 40,43 and F. fujikuroi. 41 In the study, although the deletion of CiCYP51B or CiCYP51C would increase sensitivities to several DMIs, the mutants ΔCiCYP51A, ΔCiCYP51AB, and ΔCiCYP51AC were hypersensitive to all tested DMIs, and overexpression of CiCYP51A was induced by DMIs in vitro. Furthermore, during the infection on soybean hypocotyls, the expression of CiCYP51A was dramatically upregulated in planta under the DMI-treatment conditions.…”
Section: ■ Discussionmentioning
confidence: 84%
“…acutatum, Venturia inaequalis, Penicillium digitatum, , and F. fujikuroi . In the study, although the deletion of CiCYP51B or CiCYP51C would increase sensitivities to several DMIs, the mutants ΔCiCYP51A , ΔCiCYP51AB , and ΔCiCYP51AC were hypersensitive to all tested DMIs, and overexpression of CiCYP51A was induced by DMIs in vitro .…”
Section: Discussionmentioning
confidence: 99%